Direct measurement of plume velocity to characterize point source emissions - Michael L. Eastwood; David R. Thompson; Robert O. Green; Jay E. Fahlen; Taylor J. Adams; Adam R. Brandt; Philip G. Brodrick; Adam Chlus; Eric A. Kort; Frances Reuland; Andrew K. Thorpe (Proceedings of the National Academy of Sciences, 2025)
An explosion of recent research uses remote imaging spectroscopy from aircraft and spacecraft to detect and quantify methane point source emissions. These instruments first map the methane enhancement field and then combine this information with the effective wind speed to estimate the source emission rate. This wind speed is typically the largest uncertainty in derived emission rates. It is often, by necessity, inferred from coarse-resolution meteorological reanalysis products which do not match the spatial or temporal extent of wind experienced by the gas plume. Here, we circumvent this problem by simultaneously measuring plume velocity using the same spectrometer that maps the methane plume. Our approach acquires multiple consecutive views of the same point source, with visual tracking of the plume’s features to estimate its ground velocity. This resolves the representational mismatch between reanalysis and effective wind speeds. It provides data with exact spatiotemporal coincidence to the plume being measured. The approach facilitates dramatic improvement in the precision of remote methane point source quantification.